Brief instrumental school-based mentoring for middle school students: theory and impact. Issue 2 (2nd April 2016) - McQuillin, Samuel D.; Lyons, Michael D.
Abstract: This study evaluated the efficacy of an intentionally brief school-based mentoring program. This academic goal-focused mentoring program was developed through a series of iterative randomized controlled trials, and is informed by research in social cognitive theory, cognitive dissonance theory, motivational interviewing, and research in academic enablers. In previous research, the program was found to produce effects on students' math grades, life satisfaction, and disruptive behavior. In the current study, a revised version of the program was tested in a randomized controlled trial, wherein 72 middle school students were randomly assigned to receive an eight-week mentoring curriculum, or to a no-treatment control. Following the treatment, middle school students who participated in the mentoring curriculum had statistically significantly higher math grades ( d = .42), English grades ( d = .59), life satisfaction ( d = .49), and .82 fewer absences. Small, but not statistically significant effects were also found for science ( d = .25) and history ( d = .15). Near zero effects were found for behavioral infractions.